Population characteristic of torpedo scad (Megalaspis cordyla Linnaeus, 1758) in the Lampung Bay: Size structure, growth type, and condition factor - Julian, David; Caesario, Rachmad; Kartini, Nidya; Yudha, Indra Gumay; Delis, Putu Cinthia; Hasani, Qadar; Yulianto, Herman (Universitas Malikussaleh, 2024)
Megalaspis cordyla, locally known as ikan bekre, stands as a crucial economic species commonly consumed by the people of Lampung. The escalating demand for this fish has significant implications for increased fishing activities, potentially impacting its population. This research aimed to explore the biological characteristics of M. cordyla landed at the Lempasing Fishing Port, Bandar Lampung, providing fundamental insights for fisheries resource management in the waters of Lampung Bay. Using a quantitative descriptive method, the sampled fish has been analyzed to get size structure, growth type, and fish condition factors based on length and weight data collected from M. cordyla landed weekly. Between April and June 2022, a total of 300 samples were collected, with length ranging from 230 to 430 mm TL, with the largest count (77 individuals) in the 314-334 mm interval. M. cordyla has an allometric negative growth pattern in Lampung Bay, with a growth coefficient (b) value of 2.47. Fish condition factor values ranged from 0.71 to 1.33, with June having the highest average value of 1.03. This information contributes greatly to a better understanding and long-term planning for the management of this fish population.Keywords: Allometric; Condition Factor; Length-Weight Relationship; Pelagic Fish; Aquatic Resources Management